An Analysis of the Role of School Culture in Shaping the Religious Character of Students at Tadika and Taska TKC Educare Kuala Lumpur Malaysia - Dinda Aulia; Munawir Pasaribu (Bulletin of Science Education, 2025)
Education serves a pivotal role in shaping the religious character of students, establishing a fundamental foundation for a generation imbued with morals and noble virtues. The culture within a school represents a strategic approach to actualizing this objective. the school culture encompasses various practices, such as the students' customs of greeting, kissing the teacher's hand, performing the dhuha prayer, reciting prayers, and chanting shalawat. These practices are consistently applied and significantly contribute to the formation of students' religious character, exemplified by traits such as politeness, gratitude, seeking permission, and the habit of offering apologies. The primary aims of this research are to examine the implementation process of school culture, its influence on the development of religious character, and the specific religious traits fostered in students. This study employs a descriptive method with a qualitative approach. This study was conducted at Tadika and Taska TKC Educare in Kuala Lumpur, Malaysia, with the intention of elucidating the role of school culture in cultivating students' religious character. Data were gathered through interviews with the principal and team leader, direct observations in the field, and documentation during the execution of the International Teaching Assistance programme. Data analysis was conducted using the Miles and Huberman interactive model, which encompasses data reduction, data presentation, and conclusion drawing. The school culture at Tadika and Taska TKC Educare proves to be effective in shaping students' religious character. These findings underscore the significance of consistently reinforcing school culture to instil religious values from an early age.